The Effect of Information Technology Sophistication, Top Management Support, and Personal Capability on Accounting Information System Performance in Cooperatives : (A Case Study on Savings and Loan Cooperatives in Badung Regency) - I Komang Jinarta; Ni Ketut Lely Aryani Merkusiwati (International Forum of Researchers and Lecturers, 2025)
The development of information technology has had a significant effect on the management of accounting information systems (AIS) within organizations, including Savings and Loan Cooperatives (KSP). This study aims to obtain empirical evidence regarding the effect of information technology sophistication, top management support, and personal capability on the performance of accounting information systems (AIS) in Savings and Loan Cooperatives (KSP) in Badung Regency. The implementation of an effective AIS is essential to enhance efficiency, accuracy, and the relevance of financial information to support managerial decision-making in the digitalization era. This study employs a quantitative approach with an associative design. The research population includes all registered and active KSP employees who have used information systems in Badung Regency, with a sample of 90 respondents determined through the purposive sampling method. Primary data were obtained through questionnaires and analyzed using multiple linear regression. The results indicate that information technology sophistication has a positive and significant effect on AIS performance, top management support has a positive and significant effect on AIS performance, and personal capability has a positive and significant effect on AIS performance.